KARAKTERISTIK PENGERINGAN SAGU MENGGUNAKAN ALAT PENGERING TENAGA SURYA TIPE RAK1) - Feyta Gloria Rawung; Daniel P. M. Ludong; Lady C. Ch. E. Lengkey (COCOS, 2023)
ABSTRACT This study aims to test the performance of a solar dryer for drying sago. Performance tests include: temperature distribution pattern, relative humidity of the air in the drying chamber, changes in moisture content, drying time, and drying rate. The benefits of this research are expected to use a rack-type solar dryer to shorten the drying time and also this tool can provide an overview of the use of solar energy in the process of drying sago and drying other crops. During the drying process there has been a temperature difference between the bottom shelf, middle shelf, top shelf, chimney and ambient air temperature. The average relative humidity of the ambient air on the first day is 63.75% with a maximum condition of 67% and the lowest air relative humidity condition is 60% and the average relative humidity of the air inside the device on the first day is 34.62% with a maximum condition of 37% and the lowest air relative humidity condition is 33%. The average relative humidity of the ambient air on the second day is 65.66% with a maximum condition of 69% and the lowest air relative humidity condition of 62% and the average relative humidity of the air insi de the device is 35.83% with a maximum condition of 38% and the lowest air relative humidity condition is 33%. The mathematical model of the relationship between water content and time on the bottom shelf is y = 0.6305e- 0.127x with R² = 0.972 on the middle shelf y = 0.6149e-0.118x with R² = 0.9875 on the top shelf y = 0.6434e-0.11x with R² = 0.9649. The drying rate on each shelf is different and changes occur every time because it depends on the mass of the material. The average drying rate on the lower shelf is 3.40%, the middle shelf is 3.31%, and the upper shelf is 3.21%. To reach a moisture content of 11-14% requires a total of 13 hours for 2 days. Keywoards : sago drying, rack tipe solar dryer